The Authority of the Ombudsman of the Republic of Indonesia in Supervising the Notary Supervisory Board and the Board of Trustees and Supervisors for Land Deed Making Officials (PPAT) - Andrian, Aan (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
The Ombudsman of the Republic of Indonesia is a state institution overseeing the implementation of public services. From the data from the Ombudsman RI report, there are a number of public reports regarding the services of the Notary Supervisory Council (MPN) and the PPAT Advisory & Supervisory Council (MPP PPAT). The purpose of this study is to find out and analyze the authority of the Indonesian Ombudsman in supervising the MPN and MPP PPAT in Kendari City, Southeast Sulawesi Province as well as the efforts made by the Ombudsman of the Republic of Indonesia in order to supervise and resolve allegations of maladministration committed by the MPN and MPP PPAT in Kendari City, Southeast Sulawesi Province. The approach method used in discussing this research problem is a sociological juridical approach. The specification of the research used is descriptive analytical research. Types of data using primary and secondary data. The data analysis method used is qualitative data analysis. The results of the study concluded that mutatis mutandis, the Ombudsman of the Republic of Indonesia through the Representative of the Ombudsman of the Republic of Indonesia in Southeast Sulawesi Province domiciled in Kendari City: 1) Has the authority to supervise the implementation of tasks and authorities carried out by the MPN and MPP PPAT because in their organizational structure they have elements from the government , the source of the budget comes from the State Budget (APBN) and organizes public services. in the field of public services in terms of receiving reports from the public and in the field of public administration in terms of issuing administrative decisions/decisions. 2) Oversight efforts of the Indonesian Ombudsman namely in terms of receiving, following up, and complete community reports regarding allegations of maladministration by MPN and MPP PPAT. The follow-up actions of the Ombudsman of the Republic of Indonesia include recording reports, formal and material verification of reports, requests for clarification, investigations, summons, mediation/conciliation and issuing the Final Examination Results Report (LAHP) as well as the last effort, namely Recommendations.Keywords: Ombudsman; Public; Service; Supervisory.